Serum 25(OH) Vitamin D Levels in Severely ObesePatients Evaluated Before Bariatric Surgery - (:unkn) unknown (My University, 2020)
Objective: Obesity is a risk factor for vitamin D deficiency,which is reported to be detected differently in each population. This study aimed to evaluate the 25(OH) vitamin D(25(OH)D) levels, intact parathormone (iPTH) levels, andtheir relationship with body mass index (BMI) in obese patients, screened prior to bariatric surgery. Material and Methods: This retrospective study comprised of 1.082 obesepatients (41±10 years, female/male: 823/259) who werecandidates for bariatric surgery. BMI, waist circumference(WC), serum 25(OH)D, iPTH, calcium, phosphorus values ofthese patients were recorded from patient files. Results:BMI, WC, iPTH, and 25(OH)D levels were 48±8.9 kg/m²,128±11.9 cm, 64±36 pg/mL, and 15±18 ng/mL, respectively. Mean 25(OH)D level of 79.1% of the patients belongedto the deficiency range. Very low 25(OH) vitamin D levels(<10 ng/mL) were witnessed among 40.9% (443/1.082) ofthe study group. Female obese subjects possessed significantly lower serum 25(OH)D levels as compared to maleobese patients. Significant negative correlations were perceived between 25(OH)D levels and iPTH (r=-0.34,p<0.0001), BMI (r=-0.20, p<0.0001), and waist circumferences (r=-0.14, p=0.002) in the whole group. Multivariateanalysis indicated that BMI to be an independent risk factorfor vitamin D deficiency. Conclusion: A high rate of vitaminD deficiency was documented in our morbidly obese patientswho were candidates for bariatric surgery. BMI is a determinant of 25(OH)D levels. It is essential to screen for vitaminD deficiency and possible osteomalacia among the candidates for bariatric surgery of obese patients and should betreated appropriately before bariatric surgery.

Amaç: Obezite, her popülasyonda farklı sıklıkta saptandığı bildirilen vitamin D eksikliği için bir risk faktörüdür. Bu çalışmada, bariatrik cerrahi öncesi değerlendirilen obez hastalarda 25(OH) vitamin D (25(OH)D) düzeyleri, intakt parathormon (iPTH) düzeyleri ve bunların beden kitle indeksi (BKİ) ile ilişkilerinin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntemler: Bariatrik cerrahi öncesinde değerlendirilen 1.082 morbid obez hasta (41±10 yaş, kadın/erkek: 823/259) verileri retrospektif olarak değerlendirildi. BKİ, bel çevresi (BÇ), serum 25(OH)D, iPTH, kalsiyum, fosfor değerleri hastaların dosyalarından kaydedildi. Bulgular: BKİ, BÇ, iPTH, 25(OH)D düzeyleri sırasıyla 48±8,9 kg/m², 128±11,9 cm, 64±36 pg/mL, 15±18 ng/mL idi. Ortalama 25(OH)D düzeylerinin, hastaların %79,1’inde yetersiz olduğu tespit edilmiştir. Çalışma grubundaki tüm hastaların %40,9’unda (443/1.082) çok düşük 25(OH)D vitamini seviyesi (<10 ng/mL) vardı. Obez kadınlarda 25(OH)D vitamin düzeyleri, obez erkeklere kıyasla anlamlı olarak düşük bulunmuştur. 25(OH)D vitamin düzeyleri iPTH ile ters orantılı izlenmiştir (r=-0,34, p<0,0001), tüm grupta 25(OH)D vitamin düzeyleri BKİ ve BÇ ile negatif korelasyon göstermiştir (r=-0,20, p<0,0001) (r=- 0,14, p=0,002). Multivaryant analiz, BKİ’nin D vitamini eksikliği için bağımsız bir risk faktörü olduğunu göstermektedir. Sonuç: Bariatrik cerrahi için aday olan morbid obez hastalarımızda yüksek oranda D vitamini eksikliği gözlemledik. BKİ, 25(OH)D seviyelerinin belirleyicisidir. BKİ ile 25(OH)D vitamin düzeyleri negatif korelasyon göstermektedir. Bariatrik cerrahiye aday olan obez hastalar, D vitamini eksikliği ve olası osteomalazi açısından değerlendirilmeli ve bariatrik cerrahi öncesi uygun şekilde tedavi edilmelidir.
Bariatrik Cerrahi Öncesi Değerlendirilen Ciddi Obezitesi Olan Hastalarda Serum 25(OH) Vitamin D Seviyeleri